Entrepreneurship Opportunity in Dairy Sector - SINGH, Ashish Kumar; Deshwal, Gaurav Kr; Raju, P N (Indian Farming, 2020)
Livelihood security in rural sector of India primarily depends on agriculture including livestock sector. The milk alone accounts for 67% of the value of output from livestock sector and with increasing widespread demand it will continue to be among the major contributors to rural economy. About 70 million small and marginal farmers with an average of 2-3 animals produce more than 50% of the milk in the country. Milk and milk products constitute the major share in Indian food basket, next only to rice and wheat. India contributes to about 18.4% of global milk production with over 187.74 MT in 2018-19 with an annual growth rate of nearly 6.0%. The projected demand of milk offers new opportunities for marginal and small dairy farmers.